2021
DOI: 10.1111/azo.12405
|View full text |Cite
|
Sign up to set email alerts
|

Musculature of the male abdominal segments and terminalia of Tachina nupta Rondani (Diptera: Tachinidae)

Abstract: The abdominal and pregenital segments and genitalia were studied in males of Tachina nupta Rondani, 1859. The examined species is very similar in the structure of the sclerites and muscles of their terminal segments to Calliphora erythrocephala Meigen, 1826 previously studied by R. Salzer. Despite the same set of pregenital muscles, a completely membranous tergite VI was found in Tachina in contrast to Calliphora. The discovery of membranous tergite VI in Tachina nupta indicates that it was not included in the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 9 publications
(22 reference statements)
1
6
0
Order By: Relevance
“…Within the Oestroidea that have been studied, the largest set of muscles of the hypandrial complex was found by Salzer [43] in Calliphora erythrocephala (Meigen, 1826), and this set was the same as in Delia platura. The same set of muscles of the hypandrial complex was also found in Tachina [44] except for a pair of postgonite muscles M 2 4 , which is absent in this genus.…”
Section: Discussionsupporting
confidence: 61%
See 3 more Smart Citations
“…Within the Oestroidea that have been studied, the largest set of muscles of the hypandrial complex was found by Salzer [43] in Calliphora erythrocephala (Meigen, 1826), and this set was the same as in Delia platura. The same set of muscles of the hypandrial complex was also found in Tachina [44] except for a pair of postgonite muscles M 2 4 , which is absent in this genus.…”
Section: Discussionsupporting
confidence: 61%
“…The Fanniidae have three pairs of muscles M 19 (paired M 19 1 and unpaired M 19 2 ) as do primitive Muscidae [39], Tachina [44] and Calliphora [43]. This character state we consider plesiomorphic for the Calyptrata.…”
Section: Discussionmentioning
confidence: 87%
See 2 more Smart Citations
“…In previous studies by the authors, the apomorphic transformations of the muscles of the pregenital segments of males important in the phylogenetic branching of the Calyptratae have been identified. It was shown that characters of sclerites and muscles of the pregenital segments of this group were more important in constructing suprafamily phylogeny than the transformations of the genital sclerites and muscles (Ovtshinnikova et al, 2018, 2019; Ovtshinnikova & Sorokina, 2020, 2021; Sorokina & Ovtshinnikova, 2020, 2022). However, the pregenital muscles have not been thoroughly studied in the Anthomyiidae and the Scathophagidae.…”
Section: Introductionmentioning
confidence: 99%